A Case of Diffuse Large B Cell Lymphoma of the Breast with Predominantly High-Level Internal Echoes - Masafumi Tomita (Case Reports in Oncology, 2020)
A 70-year-old woman had a large mass in her right breast. Mammography displayed focal asymmetrical density in the scattered areas of fibroglandular density. Ultrasonography showed the tumor to have predominantly high-level internal echoes. Histological examination showed that the tumor was composed of CD20-positive atypical cells with a large nucleus, scant cytoplasm, and abundant mitoses accompanied by a lot of fat cell interspersion and the diagnosis of diffuse large B cell lymphoma was made. We considered that the massive back scattering generated by the heterogeneity of acoustic impedance between fat cells and tumor cells brought about the high-level internal echoes. The patient had undergone chemotherapy followed by radiotherapy to the breast and regional nodes and has been well without lymphoma recurrence for more than 6 years. Although breast malignant lymphoma generally shows very low-level internal echoes, it could have high-level internal echoes especially in case of a non-dense breast.